Topiramate Versus Acetazolamide for Idiopathic Intracranial Hypertension. A Real-World Data-Based Multicenter Retrospective Study - Morsy, Mahmoud Mohamed; Azzam, Ahmed Yasser; Essibayi, Muhammed Amir; Abadi, Alsaleem Mohammed; Alsabaani, Nasser Abdulmohsen; Alsaleem, Safar Abadi; Aldhabaan, Waleed Abdulwahab; Abukhadijah, Hana Jihad; Morsy, Mohamed Darwesh; Garg, Aayushi Aarav; Altschu, David Joseph (Indian Journal of Pharmaceutical Education and Research)
Introduction: Idiopathic Intracranial Hypertension (IIH) is a condition marked by elevated intracranial pressure without mass lesions or hydrocephalus, primarily affecting young obese women. Acetazolamide has been the standard treatment, but its side effects often limit use. Topiramate, an anticonvulsant, has gained attention for its dual role as a carbonic anhydrase inhibitor and weight loss promoter. This study compares the efficacy and safety of topiramate versus acetazolamide in IIH management. Materials and Methods: This international, multicenter retrospective study analyzed electronic health records of IIH patients from 2009 to 2024 across six countries. Propensity score matching balanced baseline characteristics between groups, with outcomes evaluated over 24 months. Primary endpoints included papilledema resolution, headache control, visual outcomes and the incidence of refractory IIH and surgical interventions. Results: In a cohort of 16,654 propensity-matched patients (8,327 per group), topiramate significantly reduced persistent papilledema at 24 months (16.8% vs. 28.8%; p<0.0001) and improved headache control (61.2% vs. 71.3%; p<0.0001). Fewer patients in the topiramate group developed refractory IIH or required surgical interventions, such as therapeutic spinal punctures and optic nerve sheath fenestration (p<0.0001). Conclusion: Topiramate demonstrated superior efficacy compared to acetazolamide in resolving papilledema, controlling headaches and reducing the need for invasive procedures. It may represent a more effective first-line therapy for IIH. Further randomized trials are needed to validate these findings and optimize treatment protocols.
Keywords: Acetazolamide; Idiopathic Intracranial Hypetension; Papilledema; Pseudotumor Cerebri; Topiramate.